The Role of Busuu Application in Enhancing English Learning Experiences - Hidayatunnisa, Lu Lu U; Laja, Naela; Ananda, Tania; Yuliati, Yuliati; Ma'rufah, Desi Wijayanti (UM Purwokerto Press, 2025)
In the Era of Technological Advancement, Gadgets Play an Important Role in Various ActivitiesThis includes learning. With various applications offered by platform providers, both on Android and iOS, people can now learn something independently. Busuu is an application developed to help individuals learn foreign languages independently, for example, learning English on their own. The learning levels used in this application adhere to international standards, ranging from beginner level (A1), elementary level (A2), intermediate level (B1), to upper-intermediate level (B2). This application provides learning materials in audiovisual formats that enhance four English language skills. The optimization of using the Busuu application makes it highly possible for someone to prepare themselves to communicate in English. This study employs a quantitative approach with a population of 4,818 and a sample size of 20 respondents using random sampling. The data analysis techniques used are regression tests and multiple correlation analyses. The respondents in this study are users of the Busuu applicationThe test results indicate that: Simultaneously, there is an influence between variable X and variable Y with a significance value of 0.000.Partially, there is no influence of variable X1 on variable Y with a significance value of 0.054, there is an influence of variable X2 on variable Y with a significance value of 0.030, and there is an influence of variable X3 on variable Y with a significance value of 0.000.